Silicon nitride gradient structure bioceramic and preparation method thereof

Through the preparation method of silicon nitride gradient structure bioceramics, combined with modified silicone resin and polymethyl methacrylate microspheres, the problems of high hardness, low toughness and insufficient mechanical stability of composite ceramic materials in bionic bone applications are solved, and bioceramics with high toughness, good mechanical stability and bone tissue binding performance are achieved.

CN119176718BActive Publication Date: 2025-03-25SHANDONG RES & DESIGN ACADEMY OF IND CERAMICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411678054.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-25
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

Existing composite ceramic materials have problems of high hardness and low toughness in bionic bone applications, which are prone to cracking during processing, and have insufficient mechanical stability and binding performance in the human body.

Method used

By using the preparation method of silicon nitride gradient structure bioceramics, the outer bearing layer and inner contact layer are prepared, and materials such as modified silicone resin and polymethyl methacrylate microspheres are used to achieve the combination of the dense outer bearing layer and the porous inner contact layer, thereby improving the toughness and mechanical stability of the bioceramics.

Benefits of technology

It effectively overcomes the problems of low toughness and mechanical stability of bioceramics, improves the binding stability between different functional layers, avoids stratification and interface cracking, and enhances the binding performance with human skeleton tissue.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention provides a silicon nitride gradient structure bioceramic and a preparation method thereof, which belongs to the field of bioceramics. The preparation method of the silicon nitride gradient structure bioceramic consists of the following steps: preparing an outer bearing layer slurry, grouting molding, preparing an inner contact layer filler, filling molding, and post-processing. The silicon nitride gradient structure bioceramic and the preparation method thereof of the present invention effectively overcome the low toughness defect of bioceramics, improve its toughness, ensure its bearing performance in the human body, improve its mechanical stability, while improving the bonding stability between different functional layers of bioceramics, eliminating stress concentration defects, improving the overall stability of bioceramics, avoiding stratification and interface cracking problems between different functional layers; and further improving the bonding performance of bioceramics with human bone tissue to ensure good growth of human bone tissue in contact with it.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of bioceramics, and in particular to a silicon nitride gradient structure bioceramic and a preparation method thereof. Background Art

[0002] With the continuous development of science and technology and medicine, life expectancy is increasing, and osteoarthritis of the elderly is becoming more and more serious. At the same time, accidents in industry, transportation, and sports can also cause bone trauma in the human body. These bone trauma problems affect the quality of human life. The implantation or replacement of bionic bones can effectively relieve people's pain and improve the quality of life of patients with bone trauma. The materials of bionic bones in the prior art mainly include: (1) metal alloy materials such as stainless steel, titanium alloy, cobalt-chromium-molybdenum alloy; because metal alloy materials have high strength, high toughness and good processability, they have been widely used. However, metal alloy materials have problems such as easy corrosion, poor fatigue resistance, stress shielding and heavy metal ion diffusion, which limit the further application of metal alloy bionic bones. (2) Composite ceramic materials such as hydroxyapatite and silicon nitride; because composite ceramic materials have high strength, high hardness, good corrosion resistance and excellent biocompatibility, they are more suitable as bionic bones in the field of medical materials. However, existing composite ceramic materials have the characteristics of high hardness and low toughness, and are prone to cracking and breaking during processing. In addition, during actual use when implanted in the human body, they cannot effectively guarantee the mechanical properties at the load-bearing parts, have poor stability, and are at risk of fatigue cracking.

[0003] In order to solve the above technical problems, the prior art discloses the use of multilayer silicon nitride ceramic materials with different properties. By combining multilayer silicon nitride ceramics with different properties, the toughness is improved while the load-bearing performance in the human body is improved, and the mechanical stability is improved. However, due to the performance differences between the multilayer silicon nitride ceramics with different properties, the bonding stability between the layers is not good, and there is a problem of stress concentration. The overall stability of the multilayer silicon nitride ceramics is low, and there are problems of delamination and interface cracking. At the same time, the bonding performance of the multilayer silicon nitride ceramic material with human bone tissue needs to be further improved to ensure the good growth of the human bone tissue in contact with it. Summary of the invention

[0004] In order to solve the technical problems existing in the prior art, the present invention provides a silicon nitride gradient structure bioceramic and a preparation method thereof, which effectively overcomes the low toughness defect of bioceramics, improves its toughness, ensures its load-bearing performance in the human body, improves its mechanical stability, and at the same time improves the bonding stability between different functional layers of bioceramics, eliminates stress concentration defects, improves the overall stability of bioceramics, avoids stratification and interface cracking problems between different functional layers; and further improves the bonding performance between bioceramics and human bone tissue to ensure the good growth of human bone tissue in contact with it.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0006] A silicon nitride gradient structure bioceramic and a preparation method thereof, comprising the following steps: preparing an outer bearing layer slurry, grouting molding, preparing an inner contact layer filling material, filling molding, and post-processing.

[0007] The method for preparing the outer bearing layer slurry is as follows: composite silicon nitride powder, chopped alumina fiber, alumina powder, yttrium oxide powder, ammonium polyacrylate, and deionized water are put into a ball mill, the ball-to-material ratio is controlled to be 3.5-4:1, the ball milling speed is 150-200r / min, and after ball milling for 2-3h, the pH is adjusted to 10-10.5 with ammonia water with a concentration of 25-28wt% to obtain the outer bearing layer slurry.

[0008] In the slurry for preparing the outer bearing layer, the weight ratio of composite silicon nitride powder, chopped alumina fiber, alumina powder, yttrium oxide powder, ammonium polyacrylate and deionized water is 88-90:5.5-6:1.6-1.8:2-2.5:2-2.5:48-50.

[0009] The preparation method of the composite silicon nitride powder is as follows: the first silicon nitride powder and the second silicon nitride powder are put into an ethanol solution with a volume concentration of 80-85%, and after ultrasonic dispersion, the mixture is stirred and heated to 50-55°C, and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane is added dropwise while being kept warm and stirred, and the dropping time of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane is controlled to be 70-90min. After the dropping is completed, the mixture is kept warm and stirred for 4-5h, and a solid is obtained by filtering. The solid is washed with deionized water and dried to obtain the composite silicon nitride powder.

[0010] In the preparation of the composite silicon nitride powder, the weight ratio of the first silicon nitride powder, the second silicon nitride powder, the ethanol solution, and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane is 70-72:28-30:500-550:25-26;

[0011] The first silicon nitride powder is α-silicon nitride powder, and the average particle size is 0.6-0.7 μm; the second silicon nitride powder is α-silicon nitride powder, and the average particle size is 2.4-2.5 μm;

[0012] The chopped alumina fibers had a diameter of 7-8 μm and a length of 0.5-0.6 cm.

[0013] The grouting molding method is as follows: after vacuum degassing, the outer bearing layer slurry is grouted into a mold, and after standing for 3-4 hours in an environment with a temperature of 25-30°C, it is transferred to an environment with a relative humidity of 50-55% and a temperature of 30-35°C, and is left to stand for 28-30 hours to obtain an outer bearing layer blank; then the outer bearing layer blank is transferred into a sintering furnace, and in a nitrogen atmosphere, the temperature is increased to 1400-1500°C at a heating rate of 4-4.5°C / min, and the temperature is maintained for pre-sintering for 1.5-2 hours, and the outer bearing layer formed body with an open cavity is obtained.

[0014] The method for preparing the inner contact layer filler is as follows: first silicon nitride powder is added into anhydrous ethanol, and ultrasonically dispersed uniformly to obtain a silicon nitride dispersion with a solid content of 65-70wt%; then the silicon nitride dispersion and the modified silicone resin solution are added into a mixer, and the mixing speed is controlled to be 500-600r / min. After the mixing is coated for 18-20h, solid matter is obtained by centrifugation, and dried to obtain coated powder; the coated powder is evenly mixed with polymethyl methacrylate microspheres with an average particle size of 450-500μm to obtain the inner contact layer filler.

[0015] In the preparation of the inner contact layer filler, the first silicon nitride powder is α-silicon nitride powder with an average particle size of 0.6-0.7 μm;

[0016] The volume ratio of silicon nitride dispersion to modified silicone resin solution is 1.2-1.3:1;

[0017] The weight ratio of the coated powder to the polymethyl methacrylate microspheres is 4-5:1.

[0018] The preparation method of the modified silicone resin solution is as follows: hydroxypropyl methacrylate, polyethylene glycol diacrylate, triisopropylsilyl methacrylate, and 3-[tri(1-methylethoxy)silyl]propyl methacrylate are added into N,N-dimethylformamide, and the mixture is stirred evenly, and the mixture is heated to 65-70°C with stirring, and tert-butyl peroxide-2-ethylhexanoate is added dropwise while being kept warm and stirred, and the addition time of tert-butyl peroxide-2-ethylhexanoate is controlled to be 50-60min. After the addition of tert-butyl peroxide-2-ethylhexanoate is completed, the mixture is kept warm and stirred for 2-2.5h, and the mixture is heated to 85-90°C with stirring, and azobisisobutyronitrile is added, and the mixture is kept warm and stirred for 3-3.5h to obtain the modified silicone resin solution.

[0019] In the preparation of the modified silicone resin solution, the weight ratio of hydroxypropyl methacrylate, polyethylene glycol diacrylate, triisopropylsilyl methacrylate, 3-[tri(1-methylethoxy)silyl]propyl methacrylate, N,N-dimethylformamide, tert-butyl peroxy-2-ethylhexanoate, and azobisisobutyronitrile is 30-32:24-25:44-45:26-26.5:120-125:0.15-0.17:0.25-0.27.

[0020] The filling and molding method is to fill the inner contact layer filler into the open cavity of the outer bearing layer molding, then place it in a mold, control the molding pressure to 10-12MPa, perform cold isostatic pressing for 3-5 minutes, place it in an 80-90°C environment, let it stand for 12-14 hours, and demold to obtain a bioceramic molding.

[0021] The post-treatment method is to place the bioceramic molded body in a sintering furnace, heat it to 1600-1700°C at a heating rate of 2-3°C / min in a nitrogen atmosphere, sinter it for 2-3 hours, and cool it to room temperature in the furnace to obtain a silicon nitride gradient structure bioceramic with a dense outer bearing layer and a porous inner contact layer.

[0022] A silicon nitride gradient structure bioceramic is prepared by the above-mentioned preparation method.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] (1) The preparation method of the silicon nitride gradient structure bioceramic of the present invention comprises the following steps: in the step of preparing the outer bearing layer slurry, a diaminosilane coupling agent is used to modify α-silicon nitride powder with a specific particle size ratio to obtain composite silicon nitride powder, and then the composite silicon nitride powder, short-cut alumina fiber, alumina powder, yttrium oxide powder and other raw materials are combined to obtain the outer bearing layer slurry; the outer bearing layer slurry is shaped by grouting and pre-sintering to form an outer bearing layer molded body with an open cavity; various means cooperate with each other to improve the toughness, bearing performance and mechanical stability of the bioceramic, eliminate stress concentration defects, and improve the overall stability; then in the preparation of the inner contact layer filler, a modified silicone resin is first used The first silicon nitride powder is subjected to a mixing coating treatment to obtain a coated powder, and then the coated powder is evenly mixed with polymethyl methacrylate microspheres to obtain an inner contact layer filler; then, an outer bearing layer forming body with an open cavity is used as a mold, and the inner contact layer filler is filled into the open cavity of the outer bearing layer forming body, and after filling and molding, post-treatment and sintering, a silicon nitride gradient structure bioceramic with a dense outer bearing layer and a porous inner contact layer is obtained; on the one hand, a modified silicone resin prepared by combining a specific monofunctional acrylate compound, a bifunctional acrylate compound and an organic silicon monomer can improve its coating performance for the first silicon nitride powder, and can be used as The coating layer improves the bonding performance of the outer bearing layer in contact with it, avoids the delamination and cracking of the gradient structure bioceramics during preparation and use, and improves the sintering stability of the inner contact layer ceramics; on the other hand, the modified silicone resin is used as a small-pore pore-forming agent, and is combined with the macroporous pore-forming agent polymethyl methacrylate microspheres to adjust the porous distribution of the inner contact layer, thereby improving the bonding performance of the bioceramics with the human bone tissue, so as to ensure the good growth of the human bone tissue in contact with it; the aforementioned technical means cooperate and work synergistically with each other, and through a specific preparation method, the dense outer bearing layer of the bioceramics and the porous inner contact layer are effectively bonded, and the structural gradient is realized, and in the bonding with the human bone. An inner contact layer with a porous structure is used in the part to ensure the good growth of human bone tissue; and an outer bearing layer with a dense structure is used in the load-bearing part of the human bone to achieve a gradual performance gradient between different layers; it can effectively overcome the low toughness defect of bioceramics, improve its toughness, ensure its load-bearing performance in the human body, improve mechanical stability, while improving the bonding stability between different functional layers of bioceramics, eliminate stress concentration defects, improve the overall stability of bioceramics, avoid stratification and interface cracking problems between different functional layers; and further improve the bonding performance between bioceramics and human bone tissue to ensure the good growth of human bone tissue in contact with it.

[0025] (2) The preparation method of the silicon nitride gradient structure bioceramics of the present invention, the silicon nitride gradient structure bioceramics prepared has no delamination and cracking, the bending strength of the outer bearing layer is 649-656MPa, the density is 99.0-99.2%, the elastic modulus is 255-261GPa, and the fracture toughness is 7.88-7.95MPa·m 1 / 2 The bending strength of the inner contact layer is 101-104MPa, the open porosity is 40.1-40.6%, the average pore size of the macropores is 487-489μm, and the average pore size of the micropores is 1.3-1.4μm; the interface bonding strength between the outer bearing layer and the inner contact layer is 10.4-10.8MPa.

[0026] (3) The silicon nitride gradient structure bioceramics of the present invention, when subjected to a uniform load of 9000 N and maintained for 2000 h, showed no delamination or cracking.

[0027] (4) The preparation method of the silicon nitride gradient structure bioceramics of the present invention has easy-to-obtain raw materials and easy-to-control preparation process, which is conducive to large-scale industrial production. DETAILED DESCRIPTION

[0028] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0029] Example 1

[0030] This embodiment provides a method for preparing a silicon nitride gradient structure bioceramic, specifically:

[0031] 1. Preparation of external bearing layer slurry

[0032] Composite silicon nitride powder, chopped alumina fiber, alumina powder, yttrium oxide powder, ammonium polyacrylate and deionized water are put into a ball mill, the ball-to-material ratio is controlled to be 3.5:1, the ball mill speed is 150r / min, and after ball milling for 2h, the pH is adjusted to 10 with 25wt% ammonia water to prepare an outer bearing layer slurry.

[0033] Among them, the weight ratio of composite silicon nitride powder, chopped alumina fiber, alumina powder, yttrium oxide powder, ammonium polyacrylate and deionized water is 88:5.5:1.6:2:2:48.

[0034] The preparation method of composite silicon nitride powder is as follows: put the first silicon nitride powder and the second silicon nitride powder into an ethanol solution with a volume concentration of 80%, and after ultrasonic dispersion, stir and heat to 50°C, and drip N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane while keeping the temperature and stirring, and control the dripping time of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane to be 70min. After the dripping is completed, keep the temperature and stir for 4h, filter to obtain solid matter, wash the solid matter with deionized water, and dry to obtain composite silicon nitride powder.

[0035] The weight ratio of the first silicon nitride powder, the second silicon nitride powder, the ethanol solution, and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane is 70:28:500:25.

[0036] The first silicon nitride powder is α-silicon nitride powder with an average particle size of 0.6 μm; the second silicon nitride powder is α-silicon nitride powder with an average particle size of 2.4 μm.

[0037] The chopped alumina fibers had a diameter of 7 μm and a length of 0.5 cm.

[0038] 2. Grouting

[0039] After vacuum degassing, the outer bearing layer slurry is injected into the mold, and after standing for 3 hours in a temperature environment of 25°C, it is transferred to an environment with a relative humidity of 50% and a temperature of 30°C and stood for 28 hours to obtain the outer bearing layer green body; then the outer bearing layer green body is transferred into a sintering furnace, and in a nitrogen atmosphere, the temperature is increased to 1400°C at a heating rate of 4°C / min, and pre-sintered for 1.5 hours at the temperature, and cooled to room temperature with the furnace to obtain an outer bearing layer forming body with an open cavity.

[0040] 3. Preparation of inner contact layer filler

[0041] The first silicon nitride powder is added into anhydrous ethanol and uniformly dispersed by ultrasonication to obtain a silicon nitride dispersion with a solid content of 65wt%; the silicon nitride dispersion and the modified silicone resin solution are then added into a mixer, the mixing speed is controlled to be 500r / min, and the mixture is coated for 18 hours, and then the solid is obtained by centrifugation and dried to obtain a coated powder; the coated powder is uniformly mixed with polymethyl methacrylate microspheres with an average particle size of 500μm to obtain an inner contact layer filler.

[0042] The first silicon nitride powder is α-silicon nitride powder, and the average particle size is 0.6 μm.

[0043] The volume ratio of the silicon nitride dispersion to the modified silicone resin solution is 1.2:1.

[0044] The weight ratio of the coated powder to the polymethyl methacrylate microspheres is 4:1.

[0045] The preparation method of the modified silicone resin solution is as follows: hydroxypropyl methacrylate, polyethylene glycol diacrylate, triisopropylsilyl methacrylate, and 3-[tri(1-methylethoxy)silyl]propyl methacrylate are added into N,N-dimethylformamide, and the mixture is stirred evenly, and the mixture is heated to 65°C with stirring, and tert-butyl peroxide-2-ethylhexanoate is added dropwise while being kept warm and stirred, and the addition time of tert-butyl peroxide-2-ethylhexanoate is controlled to be 50 minutes. After the addition of tert-butyl peroxide-2-ethylhexanoate is completed, the mixture is kept warm and stirred for 2 hours, and the mixture is heated to 85°C with stirring, and azobisisobutyronitrile is added, and the mixture is kept warm and stirred for 3 hours to obtain a modified silicone resin solution.

[0046] The weight ratio of hydroxypropyl methacrylate, polyethylene glycol diacrylate, triisopropylsilyl methacrylate, 3-[tri(1-methylethoxy)silyl]propyl methacrylate, N,N-dimethylformamide, tert-butyl peroxy-2-ethylhexanoate, and azobisisobutyronitrile is 30:24:44:26:120:0.15:0.25.

[0047] 4. Filling and molding

[0048] The inner contact layer filler is filled into the open cavity of the outer bearing layer molding, and then placed in a mold. The molding pressure is controlled to be 10 MPa. After cold isostatic pressing for 5 minutes, it is placed in an 80°C environment, left to stand for 12 hours, and demolded to obtain a bioceramic molding.

[0049] 5. Post-processing

[0050] The bioceramic molded body is placed in a sintering furnace, and in a nitrogen atmosphere, the temperature is raised to 1600°C at a heating rate of 2°C / min, and sintered for 2 hours. The furnace is cooled to room temperature to obtain a silicon nitride gradient structure bioceramic with a dense outer bearing layer and a porous inner contact layer.

[0051] This embodiment also provides a silicon nitride gradient structure bioceramic prepared by the above method.

[0052] Example 2

[0053] This embodiment provides a method for preparing a silicon nitride gradient structure bioceramic, specifically:

[0054] 1. Preparation of external bearing layer slurry

[0055] Composite silicon nitride powder, chopped alumina fiber, alumina powder, yttrium oxide powder, ammonium polyacrylate and deionized water are put into a ball mill, the ball-to-material ratio is controlled to be 3.7:1, the ball mill speed is 180r / min, and after ball milling for 2.5h, the pH is adjusted to 10.2 with 25wt% ammonia water to prepare the outer bearing layer slurry.

[0056] Among them, the weight ratio of composite silicon nitride powder, chopped alumina fiber, alumina powder, yttrium oxide powder, ammonium polyacrylate and deionized water is 89:5.8:1.7:2.3:2.2:49.

[0057] The preparation method of composite silicon nitride powder is as follows: put the first silicon nitride powder and the second silicon nitride powder into an ethanol solution with a volume concentration of 82%, and after ultrasonic dispersion, stir and heat to 52°C, and drip N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane while keeping the temperature and stirring, and control the dripping time of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane to be 80min. After the dripping is completed, continue to keep the temperature and stir for 4.5h, filter to obtain solid matter, wash the solid matter with deionized water, and dry to obtain composite silicon nitride powder.

[0058] The weight ratio of the first silicon nitride powder, the second silicon nitride powder, the ethanol solution, and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane is 71:29:530:25.5.

[0059] The first silicon nitride powder is α-silicon nitride powder with an average particle size of 0.6 μm; the second silicon nitride powder is α-silicon nitride powder with an average particle size of 2.4 μm.

[0060] The chopped alumina fibers had a diameter of 7 μm and a length of 0.5 cm.

[0061] 2. Grouting

[0062] After vacuum degassing, the outer bearing layer slurry is injected into the mold, and after standing for 3.5 hours in a temperature environment of 27°C, it is transferred to an environment with a relative humidity of 52% and a temperature of 32°C and stood for 29 hours to obtain the outer bearing layer green body; then the outer bearing layer green body is transferred into a sintering furnace, and in a nitrogen atmosphere, the temperature is increased to 1450°C at a heating rate of 4.3°C / min, and pre-sintered for 1.8 hours at the temperature, and cooled to room temperature with the furnace to obtain an outer bearing layer formed body with an open cavity.

[0063] 3. Preparation of inner contact layer filler

[0064] The first silicon nitride powder is added into anhydrous ethanol and uniformly dispersed by ultrasonication to obtain a silicon nitride dispersion with a solid content of 68 wt%; the silicon nitride dispersion and the modified silicone resin solution are then added into a mixer, the mixing speed is controlled to be 550 r / min, and the mixture is coated for 19 hours, and then the solid is obtained by centrifugation and dried to obtain a coated powder; the coated powder is uniformly mixed with polymethyl methacrylate microspheres with an average particle size of 500 μm to obtain an inner contact layer filler.

[0065] The first silicon nitride powder is α-silicon nitride powder, and the average particle size is 0.6 μm.

[0066] The volume ratio of the silicon nitride dispersion to the modified silicone resin solution is 1.25:1.

[0067] The weight ratio of the coated powder to the polymethyl methacrylate microspheres is 4.5:1.

[0068] The preparation method of the modified silicone resin solution is as follows: hydroxypropyl methacrylate, polyethylene glycol diacrylate, triisopropylsilyl methacrylate, and 3-[tri(1-methylethoxy)silyl]propyl methacrylate are added into N,N-dimethylformamide, and the mixture is stirred evenly, and the mixture is heated to 68°C with stirring, and tert-butyl peroxide-2-ethylhexanoate is added dropwise while being kept warm and stirred, and the addition time of tert-butyl peroxide-2-ethylhexanoate is controlled to be 55 minutes. After the addition of tert-butyl peroxide-2-ethylhexanoate is completed, the mixture is kept warm and stirred for 2.2 hours, and the mixture is heated to 88°C with stirring, and azobisisobutyronitrile is added, and the mixture is kept warm and stirred for 3.2 hours to obtain the modified silicone resin solution.

[0069] The weight ratio of hydroxypropyl methacrylate, polyethylene glycol diacrylate, triisopropylsilyl methacrylate, 3-[tri(1-methylethoxy)silyl]propyl methacrylate, N,N-dimethylformamide, tert-butyl peroxy-2-ethylhexanoate, and azobisisobutyronitrile is 31:24.5:44.5:26.3:123:0.16:0.26.

[0070] 4. Filling and molding

[0071] The inner contact layer filler is filled into the open cavity of the outer bearing layer molding, and then placed in a mold. The molding pressure is controlled to be 11 MPa. After cold isostatic pressing for 4 minutes, it is placed in an 85°C environment, left to stand for 13 hours, and demolded to obtain a bioceramic molding.

[0072] 5. Post-processing

[0073] The bioceramic formed body is placed in a sintering furnace, and in a nitrogen atmosphere, the temperature is raised to 1650°C at a heating rate of 2.5°C / min, and sintered for 2.5 hours. The furnace is cooled to room temperature to obtain a silicon nitride gradient structure bioceramic with a dense outer bearing layer and a porous inner contact layer.

[0074] This embodiment also provides a silicon nitride gradient structure bioceramic prepared by the above method.

[0075] Example 3

[0076] This embodiment provides a method for preparing a silicon nitride gradient structure bioceramic, specifically:

[0077] 1. Preparation of external bearing layer slurry

[0078] Composite silicon nitride powder, chopped alumina fiber, alumina powder, yttrium oxide powder, ammonium polyacrylate and deionized water are put into a ball mill, the ball-to-material ratio is controlled to be 4:1, the ball mill speed is 200r / min, and after ball milling for 3 hours, the pH is adjusted to 10.5 with 25wt% ammonia water to prepare the outer bearing layer slurry.

[0079] Among them, the weight ratio of composite silicon nitride powder, chopped alumina fiber, alumina powder, yttrium oxide powder, ammonium polyacrylate and deionized water is 90:6:1.8:2.5:2.5:50.

[0080] The preparation method of composite silicon nitride powder is as follows: put the first silicon nitride powder and the second silicon nitride powder into an ethanol solution with a volume concentration of 85%, and after ultrasonic dispersion, stir and heat to 55°C, and drip N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane while keeping the temperature and stirring, and control the dripping time of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane to be 90min. After the dripping is completed, continue to keep the temperature and stir for 5h, filter to obtain solid matter, wash the solid matter with deionized water, and dry to obtain composite silicon nitride powder.

[0081] The weight ratio of the first silicon nitride powder, the second silicon nitride powder, the ethanol solution, and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane is 72:30:550:26.

[0082] The first silicon nitride powder is α-silicon nitride powder with an average particle size of 0.6 μm; the second silicon nitride powder is α-silicon nitride powder with an average particle size of 2.4 μm.

[0083] The chopped alumina fibers had a diameter of 7 μm and a length of 0.5 cm.

[0084] 2. Grouting

[0085] After vacuum degassing, the outer bearing layer slurry is injected into the mold, and after standing for 4 hours in a temperature environment of 30°C, it is transferred to an environment with a relative humidity of 55% and a temperature of 35°C, and stood for 30 hours to obtain the outer bearing layer green body; then the outer bearing layer green body is transferred into a sintering furnace, and in a nitrogen atmosphere, the temperature is increased to 1500°C at a heating rate of 4.5°C / min, and pre-sintered for 2 hours at the temperature, and cooled to room temperature with the furnace to obtain an outer bearing layer forming body with an open cavity.

[0086] 3. Preparation of inner contact layer filler

[0087] The first silicon nitride powder is added into anhydrous ethanol and uniformly dispersed by ultrasonication to obtain a silicon nitride dispersion with a solid content of 70 wt%; the silicon nitride dispersion and the modified silicone resin solution are then added into a mixer, the mixing speed is controlled to be 600 r / min, and the mixture is coated for 20 hours, and then the solid is obtained by centrifugation, and dried to obtain a coated powder; the coated powder is uniformly mixed with polymethyl methacrylate microspheres with an average particle size of 500 μm to obtain an inner contact layer filler.

[0088] The first silicon nitride powder is α-silicon nitride powder, and the average particle size is 0.6 μm.

[0089] The volume ratio of the silicon nitride dispersion to the modified silicone resin solution is 1.3:1.

[0090] The weight ratio of the coated powder to the polymethyl methacrylate microspheres is 5:1.

[0091] The preparation method of the modified silicone resin solution is as follows: hydroxypropyl methacrylate, polyethylene glycol diacrylate, triisopropylsilyl methacrylate, and 3-[tri(1-methylethoxy)silyl]propyl methacrylate are added into N,N-dimethylformamide, and the mixture is stirred evenly, and the mixture is heated to 70°C with stirring, and tert-butyl peroxide-2-ethylhexanoate is added dropwise while being kept warm and stirred, and the addition time of tert-butyl peroxide-2-ethylhexanoate is controlled to be 60 minutes. After the addition of tert-butyl peroxide-2-ethylhexanoate is completed, the mixture is kept warm and stirred for 2.5 hours, and the mixture is heated to 90°C with stirring, and azobisisobutyronitrile is added, and the mixture is kept warm and stirred for 3.5 hours to obtain the modified silicone resin solution.

[0092] The weight ratio of hydroxypropyl methacrylate, polyethylene glycol diacrylate, triisopropylsilyl methacrylate, 3-[tri(1-methylethoxy)silyl]propyl methacrylate, N,N-dimethylformamide, tert-butyl peroxy-2-ethylhexanoate, and azobisisobutyronitrile is 32:25:45:26.5:125:0.17:0.27.

[0093] 4. Filling and molding

[0094] The inner contact layer filler is filled into the open cavity of the outer bearing layer molding, and then placed in a mold. The molding pressure is controlled to be 12 MPa. After cold isostatic pressing for 3 minutes, it is placed in a 90°C environment, left to stand for 14 hours, and demolded to obtain a bioceramic molding.

[0095] 5. Post-processing

[0096] The bioceramic molded body is placed in a sintering furnace, and in a nitrogen atmosphere, the temperature is raised to 1700°C at a heating rate of 3°C / min, and sintered for 3 hours. The furnace is cooled to room temperature to obtain a silicon nitride gradient structure bioceramic with a dense outer bearing layer and a porous inner contact layer.

[0097] This embodiment also provides a silicon nitride gradient structure bioceramic prepared by the above method.

[0098] Comparative Example 1

[0099] Comparative Example 1 adopts the technical solution of Example 2, except that: 1) in the step of preparing the outer bearing layer slurry, the first silicon nitride powder is used instead of the composite silicon nitride powder; 2) in the step of preparing the inner contact layer filler, the polymethyl methacrylate microspheres are omitted, and the coated powder is used as the inner contact layer filler.

[0100] Comparative Example 2

[0101] Comparative Example 2 adopts the technical solution of Example 2, except that: 1) in the step of preparing the outer bearing layer slurry, the second silicon nitride powder is omitted in the preparation of the composite silicon nitride powder; 2) in the step of preparing the inner contact layer filler, the addition of the modified silicone resin solution is omitted, and the first silicon nitride powder and polymethyl methacrylate microspheres are evenly mixed to obtain the inner contact layer filler.

[0102] The outer bearing layer and the inner contact layer of the silicon nitride gradient structure bioceramics prepared in Examples 1-3 and Comparative Examples 1-2 were observed to see whether there was any delamination or cracking; and the bending strength, density, modulus, fracture toughness of the outer bearing layer, the bending strength, open porosity, average pore size of large pores, average pore size of small pores of the inner contact layer, and the interface bonding strength between the outer bearing layer and the inner contact layer of the silicon nitride gradient structure bioceramics prepared in Examples 1-3 and Comparative Examples 1-2 were tested.

[0103] Among them, the fracture toughness of the outer bearing layer is tested by the single-edge notched beam method (SENB method).

[0104] The specific test results are shown in the following table:

[0105]

[0106] The silicon nitride gradient structure bioceramics prepared in Examples 1-3 and Comparative Examples 1-2 were placed on a universal material testing machine, and a load of 9000N was uniformly applied. After the load was applied for 2000 hours, the outer bearing layer and the inner contact layer of each silicon nitride gradient structure bioceramic were observed to see whether there was delamination or cracking. The specific test results are shown in the following table:

[0107]

[0108] It can be seen that the preparation method of the silicon nitride gradient structure bioceramics of the present invention, in the step of preparing the outer bearing layer slurry, a diaminosilane coupling agent is used to modify α-silicon nitride powder with a specific particle size ratio to obtain composite silicon nitride powder, and then the composite silicon nitride powder, short-cut alumina fiber, alumina powder, yttrium oxide powder and other raw materials are combined to prepare the outer bearing layer slurry; the outer bearing layer slurry is slurry-casted and pre-sintered to form an outer bearing layer molded body with an open cavity; various means cooperate with each other to improve the toughness, bearing performance and mechanical stability of the bioceramics, eliminate stress concentration defects, and improve the overall stability; then in the preparation of the inner contact layer filler, a modified silicone resin is first used The first silicon nitride powder is mixed and coated with fat to obtain a coated powder, and then the coated powder is evenly mixed with polymethyl methacrylate microspheres to obtain an inner contact layer filler; then, an outer bearing layer molding with an open cavity is used as a mold, and the inner contact layer filler is filled into the open cavity of the outer bearing layer molding, and after filling and molding, post-treatment and sintering, a silicon nitride gradient structure bioceramic with a dense outer bearing layer and a porous inner contact layer is obtained; on the one hand, a modified silicone resin prepared by combining a specific monofunctional acrylate compound, a bifunctional acrylate compound and an organic silicon monomer can improve its coating performance for the first silicon nitride powder, and can be used as The coating layer improves the bonding performance of the outer bearing layer in contact with it, avoids the delamination and cracking of the gradient structure bioceramics during preparation and use, and improves the sintering stability of the inner contact layer ceramics; on the other hand, the modified silicone resin is used as a small-pore pore-forming agent, and is combined with the macroporous pore-forming agent polymethyl methacrylate microspheres to adjust the porous distribution of the inner contact layer, improve the bonding performance of the bioceramics with the human bone tissue, so as to ensure the good growth of the human bone tissue in contact with it; the aforementioned technical means cooperate and work synergistically with each other, and through a specific preparation method, the dense outer bearing layer of the bioceramics and the porous inner contact layer are effectively bonded, and the structural gradient is realized, and in the bonding with the human bone. An inner contact layer with a porous structure is used in the part to ensure the good growth of human bone tissue; and an outer bearing layer with a dense structure is used in the load-bearing part of the human bone to achieve a gradual performance gradient between different layers; it can effectively overcome the low toughness defect of bioceramics, improve its toughness, ensure its load-bearing performance in the human body, improve mechanical stability, while improving the bonding stability between different functional layers of bioceramics, eliminate stress concentration defects, improve the overall stability of bioceramics, avoid stratification and interface cracking problems between different functional layers; and further improve the bonding performance between bioceramics and human bone tissue to ensure the good growth of human bone tissue in contact with it.

[0109] Unless otherwise specified, all percentages used in the present invention are by mass.

[0110] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a silicon nitride gradient structure bioceramic, characterized in that: The method comprises the following steps: preparing slurry for the outer bearing layer, grouting and forming, preparing filling material for the inner contact layer, filling and forming, and post-processing; The method for preparing the outer bearing layer slurry is to uniformly ball-mill composite silicon nitride powder, chopped alumina fibers, alumina powder, yttrium oxide powder, ammonium polyacrylate, and deionized water, and adjust the pH to 10-10.5 to obtain the outer bearing layer slurry; The preparation method of the composite silicon nitride powder comprises the following steps: adding the first silicon nitride powder and the second silicon nitride powder into an ethanol solution, dispersing them uniformly, stirring and heating to 50-55° C., dripping N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane with stirring while maintaining the temperature, continuing to maintain the temperature and stirring after the dripping is completed, separating and obtaining a solid, and washing and drying the solid to obtain the composite silicon nitride powder; The first silicon nitride powder is α-silicon nitride powder with an average particle size of 0.6-0.7 μm; the second silicon nitride powder is α-silicon nitride powder with an average particle size of 2.4-2.5 μm; The grouting molding method comprises the following steps: after vacuum degassing, the outer bearing layer slurry is grouted into a mold, and after standing in an environment with a temperature of 25-30°C, it is transferred to an environment with a relative humidity of 50-55% and a temperature of 30-35°C, and is allowed to stand to obtain an outer bearing layer blank; then, the outer bearing layer blank is transferred into a sintering furnace, and in a nitrogen atmosphere, the temperature is raised to 1400-1500°C, and pre-sintered under heat preservation to obtain an outer bearing layer formed body with an open cavity; The method for preparing the inner contact layer filler comprises: adding a first silicon nitride powder into anhydrous ethanol, dispersing it uniformly, and obtaining a silicon nitride dispersion; then mixing the silicon nitride dispersion with a modified organic silicone resin solution for coating, separating to obtain a solid, and drying to obtain a coated powder; and uniformly mixing the coated powder with polymethyl methacrylate microspheres to obtain an inner contact layer filler; The preparation method of the modified silicone resin solution is as follows: hydroxypropyl methacrylate, polyethylene glycol diacrylate, triisopropylsilyl methacrylate, and 3-[tri(1-methylethoxy)silyl]propyl methacrylate are added to N,N-dimethylformamide, stirred evenly, heated to 65-70° C., stirred and kept warm, tert-butyl peroxy-2-ethylhexanoate is added dropwise, stirred and kept warm, then stirred and heated to 85-90° C., azobisisobutyronitrile is added, stirred and kept warm, and the modified silicone resin solution is prepared; The filling and molding method comprises filling the inner contact layer filler into the open cavity of the outer bearing layer molding body, performing cold isostatic pressing, standing, and demolding to obtain a bioceramic molding body; The post-treatment method is to heat the bioceramic molded body to 1600-1700° C. at a heating rate of 2-3° C. / min in a nitrogen atmosphere, and sinter for 2-3 hours to obtain silicon nitride gradient structure bioceramics.

2. The method for preparing the silicon nitride gradient structure bioceramic according to claim 1, characterized in that: In the slurry for preparing the outer bearing layer, the weight ratio of composite silicon nitride powder, chopped alumina fiber, alumina powder, yttrium oxide powder, ammonium polyacrylate and deionized water is 88-90:5.5-6:1.6-1.8:2-2.5:2-2.5:48-50.

3. The method for preparing the silicon nitride gradient structure bioceramic according to claim 1, characterized in that: In the preparation of the composite silicon nitride powder, the volume concentration of the ethanol solution is 80-85%; The dropping time of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane is 70-90 min; The time of heat preservation and stirring after the dropwise addition of N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane is 4-5 hours.

4. The method for preparing the silicon nitride gradient structure bioceramic according to claim 1, characterized in that: In the preparation of the composite silicon nitride powder, the weight ratio of the first silicon nitride powder, the second silicon nitride powder, the ethanol solution, and N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane is 70-72:28-30:500-550:25-26; The chopped alumina fibers had a diameter of 7-8 μm and a length of 0.5-0.6 cm.

5. The method for preparing the silicon nitride gradient structure bioceramic according to claim 1, characterized in that: In the preparation of the inner contact layer filler, the solid content of the silicon nitride dispersion is 65-70wt%; The speed of the mixed coating treatment is 500-600r / min, and the time of the mixed coating treatment is 18-20h; The average particle size of polymethyl methacrylate microspheres is 450-500 μm; The volume ratio of silicon nitride dispersion to modified silicone resin solution is 1.2-1.3:1; The weight ratio of the coated powder to the polymethyl methacrylate microspheres is 4-5:

1.

6. The method for preparing the silicon nitride gradient structure bioceramic according to claim 1, characterized in that: In the preparation of the modified silicone resin solution, the dripping time of tert-butyl peroxy-2-ethylhexanoate is 50-60 minutes; The weight ratio of hydroxypropyl methacrylate, polyethylene glycol diacrylate, triisopropylsilyl methacrylate, 3-[tri(1-methylethoxy)silyl]propyl methacrylate, N,N-dimethylformamide, tert-butyl peroxy-2-ethylhexanoate, and azobisisobutyronitrile is 30-32:24-25:44-45:26-26.5:120-125:0.15-0.17:0.25-0.

27.

7. The method for preparing the silicon nitride gradient structure bioceramic according to claim 1, characterized in that: The filling and molding method is to fill the inner contact layer filler into the open cavity of the outer bearing layer molding body, then place it in a mold, control the molding pressure to 10-12MPa, perform cold isostatic pressing, place it in an 80-90°C environment, let it stand and then demold it to obtain a bioceramic molding body.

8. A silicon nitride gradient structure bioceramic, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method for porous silicon nitride ceramic

    CN103922748A

  • Gelcasting forming method of Si3N4 porous ceramic

    CN105294111A